2006
DOI: 10.1159/000090342
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Apoptosis, Activation and Anti-Inflammatory Cytokine Response in Granulocyte Colony-Stimulating Factor-Treated Patients with Community-Acquired Pneumonia

Abstract: Background:Despite antibiotic treatment, the mortality of severe community-acquired pneumonia (CAP), especially in patients with severe comorbidity, remains high. Innate defense mechanisms including polymorphonuclear neutrophil (PMN) activation and survival, orchestrated by cytokines, are primarily responsible for the elimination of bacterial organisms from the alveolus. Objectives: The aim of this study was to evaluate the effect of granulocyte colony-stimulating factor (G-CSF) on PMN activation, apoptosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Massive numbers of neutrophils migrate to the airspaces in community-acquired pneumonia and the acute respiratory distress syndrome (ARDS), yet the burden of apoptotic cells is surprisingly low (37)(38)(39). We therefore questioned if the tonic suppression displayed by resting AMs could be overcome during acute inflammation.…”
Section: The Phagocytic Capacity Of Ams Is Enhanced During Inflammationmentioning
confidence: 99%
“…Massive numbers of neutrophils migrate to the airspaces in community-acquired pneumonia and the acute respiratory distress syndrome (ARDS), yet the burden of apoptotic cells is surprisingly low (37)(38)(39). We therefore questioned if the tonic suppression displayed by resting AMs could be overcome during acute inflammation.…”
Section: The Phagocytic Capacity Of Ams Is Enhanced During Inflammationmentioning
confidence: 99%
“…Accumulation of a particular leukocyte subset in tissue depends not only on the number of cells being recruited, but also on the number of cells that are cleared (by apoptosis) or leave the tissue (9). Recent studies have shown that apoptosis of neutrophils contributes to natural or induced (by antiinflammatory agents) resolution of inflammation (10, 11).…”
mentioning
confidence: 99%
“…Accumulation of macrophages in the affected alveoli is a general finding of lobar pneumonia. Bacterial infection initiates an acute inflammatory response characterized by rapid recruitment of macrophages and neutrophils and release proinflammatory cytokines including tumor necrosis factor–α and interleukinin–1 . These proinflammatory cytokines are necessary for local bacterial defense and clearance, but systemic overproduction of proinflammatory cytokines is thought to be a central factor in uncontrolled sepsis and septic shock.…”
Section: Discussionmentioning
confidence: 99%